BIOPESTICIDES FROM PAPAYA LEAVES AND TEMBELEKAN LEAVES TO CONTROL ARMYWORM PESTS (Spodoptera Litura F) - F Fachraniah; Asmaul Husna; E Elwina (Politeknik Negeri Lhokseumawe, 2023)
Biopesticides made from papaya leaves and tembelekan leaves to control armyworm pests (Spodoptera litura F) have been carried out, these two plants are relatively easy to find around us and contain active compounds that have the potential as insecticides. Plant extracts are obtained by maceration using ethanol solvent p.a, then evaporated to separate the extract and solvent so that an extract is obtained. The variables of the study conducted were the composition of P100: T10, P90: T10, P80: T20, P70: T30, and P0: T100. Soaking time 1-4 days and applied to armyworm (Spodoptera litura F) for 2 hours. The results of the study reached the quality of P100:T0 and P90 biopesticides; T10 with a soaking time of 1-3 days obtained an average armyworm mortality of 88.6%. The characteristics of biopesticides produced from tannin levels and flavonoid levels have a positive correlative relationship with the mortality power of gryak caterpillars (Spodoptera litura F), P100: T0 there are 0.0366% tannin levels and 1.58% flavonoid levels with 76% mortality power and P90:T10 there are 0.03725 tannin levels and 1.6394% falvonoid levels with 100% mortality power.Â Keywords: Biopesticides, Mortality, and Spodoptera litura F